Imitation in immigrant entrepreneurship: an analytical framework. Issue 5 (24th June 2020) - Glinka, Beata; Hensel, Przemysław G.
Abstract : Purpose: The phenomenon of imitation has attracted immense attention in studies of big companies, but it has been largely neglected in the immigrant entrepreneurship research thus far. The purpose of this paper is to address that gap by proposing a theoretical framework for studying immigrant entrepreneurship imitation decisions. Design/methodology/approach: The framework is based on a review of relevant literature covering the issue of imitation within three perspectives: institutional, heuristics of judgement and organisational learning. We validate the framework by juxtaposing it with existing studies on immigrant entrepreneurship, where imitation practices were directly and indirectly referred to. The framework is also initially validated with data from three qualitative studies performed by the authors. Findings: The literature-derived framework consists of three major building blocks (i.e. causes, target and content of imitation) while immigrant-entrepreneurship specificity (ethnic groups and clusters, ethnic identity, generation, and resources) constitutes the context of the framework. The authors formulate 12 propositions on which the framework is based. The specific character of immigrant entrepreneurs' imitation decision is discussed, and differences in that regard between immigrant entrepreneurs and established local businesses are highlighted. Research limitations/implications: A more diversified sample and quantitative studies are needed to further verify the proposed framework and propositions. Social implications: The framework is intended to expedite future research on immigrant entrepreneurs' imitative decisions and facilitate better-adjusted public policy to support immigrant entrepreneurs. Originality/value: This paper drives attention to a widely used, yet understudied phenomenon of imitation, provides an analytical framework for the study of imitation in immigrant entrepreneurship, provides a preliminary validation of the framework and contributes to a better understanding of immigrant behaviour.